Complementary feeding practices among rural Bangladeshi mothers: Results from WASH Benefits study. Issue 1 (13th August 2018) - Jannat, Kaniz; Luby, Stephen P.; Unicomb, Leanne; Rahman, Mahbubur; Winch, Peter J.; Parvez, Sarker M.; Das, Kishor K.; Leontsini, Elli; Ram, Pavani K.; Stewart, Christine P.
Abstract: Inappropriate complementary feeding contributes to linear growth faltering in early childhood. Behaviour change interventions have been effective at improving practice, but few studies have investigated the effects of multicomponent integrated interventions. We conducted a cluster‐randomized controlled trial in rural Bangladesh in which geographic clusters were randomized into seven arms: water treatment (W), sanitation (S), handwashing (H), water, sanitation, and handwashing (WSH), improved nutrition with infant and young child feeding messages and lipid‐based nutrient supplementation for 6‐ to 24‐month olds (N), N+WSH, and control. The objective of this paper was to examine the independent and combined effects of interventions on indicators of complementary feeding. Approximately 1 and 2 years after initiation of the intervention, research assistants surveyed mothers about infant feeding practices. Complementary feeding was examined using the World Health Organization indicators of infant and young child feeding practices. We used Poisson regression models to estimate prevalence ratios and linear regression models for prevalence differences with clustered sandwich estimators to adjust for clustering. A total of 4, 718 households from 720 clusters were surveyed at year 1 and 4, 667 at year 2. The children in the nutrition arms had a higher prevalence of meeting the minimum dietary diversity score compared with controls (year 1: N: 66.4%; N+WSH: 65.0% vs. C:32.4%; year 2: N: 91.5%; N+WSH: 91.6% vs. C:77.7%). Children in the nutrition arms received diverse food earlier than the children in control arm. In addition, the average consumption of lipid‐based nutrient supplementation was >90% in each follow‐up. Nutrition‐specific interventions could be integrated with nutrition‐sensitive interventions such as WSH without compromising the uptake of the nutrition intervention.